Translating the Autobiography as a Human Experience: A Case Study of Barack Obama’s Autobiographical Novel ‘Dreams from My Father: A Story of Race and Inheritance’ - Soumaya, MAZOUZ (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
المقال دراسة تحليلية لترج التالي تحت عنوان 'ترجمة أسلوب السرد القصصي      في السيرة الذاتية كتجربة إنسانية” دراسة السيرة الذاتية لباراك أوباما في روايته أحلام من أبي: قصة عرق وإرث" والذي ترجمها إلى العربية هبة السيد، نجيب المغربي، وإيمان عبد الغني نجم, المقال دراسة تحليلية. الترجمة الأدبية وخاصة ترجمة السير الذاتية الذين يهرع ون في أعمالهم للاستناد        إلى النظريات الترجمية بدلا من اللجوء       إلى القدرات والمهارات الخلاقة الموجودة فيهم أصلا بالفطرة. فبعد التطرق إلى بعض الحالات والتجارب الترجمية خرجنا بأنه لا وجود لنظرية ترجمية متكاملة وأن كل مترجم قادر على ابتكار طريقة معينة أو تقنيات محددة لنقل النصوص من لغة إلى لغة أخرى. كما أننا وجدنا أن الإنسان قادر أن يعيش تجارب الناس لأنها منبثقة من واقع الإنسانية وبذلك فهو قادر أن يلبس جلد الكاتب الأصلي للسيرة          و يترجمها ترجمة فطرية فتكون قريبة جدا   من السيرة الحقيقية بدل التشدق في استعمال نظريات الترجمة المقننة. The article is about the analysis of a translation into Arabic by Hiba Assayid Nadjib Maghribi and Imen Abdelghani Nadjm of President Barack Obama’s autobiographical work entitled: ‘Dreams from My Father.’ Obama is not only a writer but also the current president of the United States of America. This analysis attempts to show point out some shortcomings in the Arabic translation and demonstrate how translators commonly tend to draw on traditional theories of translation in their works, thus neglecting to exploit their own creativity. As a result, this Arabic translation of the novel partly failed to highlight the author’s own life experience that he attempted to reflect throughout his narrative. Though no translation method is ultimately perfect, one translator can, however, devise one’s own technique for either communicating with readers speaking a different language, or transmitting whatever message from a source language into a target one, using one’s own emotions and style to convey one’s message to the readers as clearly as possible.